Performance of Business: A Review of The Literature - Artha, Bhenu; Satriadhi, Bintoro (LLDIKTI Wilayah 1 Sumatera Utara, 2023)
Business performance, in general, consists of two components: financial performance and non-financial performance, and it is critical to control and combine the two types of performance for start-up development. Financial performance refers to firm performance that can be measured in terms of money value and financial operations, whereas non-financial performance refers to firm performance that cannot be measured in terms of money value, such as brand reputation, customer satisfaction, organizational performance, and innovation activities. The purpose of this study was to determine the variables related to business performance. This research is a literature study, which uses 20 articles as study material. The results of this study indicate the variables related to business performance. This study did not find business performance used as a moderating variable, which can be used as research material in the future.